Interprofessional Education Between Biomedical Engineering and Health Sciences - Rios, Mariana; Perdiz, Natalia P.; Aversano, Florencia; Ulla, Marina; Risk, Marcelo R. (Revista del Hospital Italiano de Buenos Aires, 2024)
Interprofessional education is related to educational scenarios where professionals or students from different areas of knowledge learn with, from and about each other to improve the quality of health care. In this paper we describe our educational experiences, carried out at the Universidad Hospital Italiano de Buenos Aires.